PENGARUH REWARD, PUNISHMENT, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. KANAAN GLOBAL INDONESIA TELUKAN SUKOHARJO - Yeni Kusuma Wardani; Sri Hartono; Raisa Aribatul Hamidah; Fithri Setya Marwati (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to identify and analyze the effect of reward, punishment, and work discipline on employee performance at PT. Kanaan Global Indonesia Telukan Sukoharjo, both partially and simultaneously. The study employed a quantitative approach using a survey method. The population consisted of 2,000 employees, while the sample comprised 100 respondents determined using the Slovin formula and selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, the F-test, the t-test, and the coefficient of determination (R²) with the assistance of SPSS software. The findings reveal that reward, punishment, and work discipline each have a positive and statistically significant effect on employee performance, with punishment showing the most dominant contribution. The Adjusted R² value of 0.832 indicates that 83.2% of the variation in employee performance can be explained by the three independent variables, whereas the remaining 16.8% is attributable to other factors beyond the scope of this study, such as work motivation, work environment, and leadership style. Keywords: reward, punishment, work discipline, employee performance